The Lipopolysaccharide of Haemophilus parainfluenzae - Young, R (2011)
Haemophilus parainfluenzae (Hp) and H. influenzae (Hi) are closely related members of the Pasteurellaceae family and are common commensal bacteria of the human nasopharynx. Whilst Hi is frequently implicated in meningitis, otitis media and respiratory tract infections, reports of pathogenic behaviour by Hp are very rare. Lipopolysaccharide (LPS) is a key component of the Gram negative cell wall, and its structure influences the ability of Haemophilus to interact with the host and evade immune clearance. A better understanding of the differences in LPS structure between Hi and Hp could help to ascertain which parts of the molecule are important for commensal and pathogenic behaviour. Hi LPS comprises lipid A, a conserved oligosaccharide inner core, and an oligosaccharide outer core that differs between strains. The latter is partly phase variable by the slipped strand mispairing during replication of DNA repeat tracts within several LPS biosynthesis genes. Very little was known about LPS in Hp so we investigated its biosynthesis and structure in a panel of 20 Hp carriage isolates. Using PCR, DNA sequencing and Southern analysis we demonstrated that Hp possesses homologues of the Hi lipid A and inner core LPS synthesis genes and a few of the genes for outer core synthesis; however, homologues of the Hi phase variable outer core genes were largely absent and did not contain repeat tracts. The results of immunoblotting and collaborative structural analysis were consistent with this data. Phosphocholine, a phase variable Hi LPS epitope that has been implicated in otitis media, was found to be absent in Hp LPS due to the lack of four genes required for its biosynthesis and incorporation. The introduction of these genes into Hp led to the phase variable addition of phosphocholine to the LPS, indicating that there is no fundamental reason why Hp could not use a similar mechanism of variation to Hi if it was advantageous to do so. SDS-PAGE data suggested the presence of O-antigens (repeated chains of sugars) in many of the Hp strains, an unusual feature for Haemophilus, and all of the strains were found to contain a potential O-antigen synthesis locus. Each locus encodes homologues of several glycosyltransferases in addition to either the Wzy polymerase- or ABC transporter-dependent mechanisms of O-antigen synthesis and transport. Comparisons of wild type and isogenic mutant strains showed that the O-antigen enhances resistance to complement-mediated killing and appears to affect adhesion to epithelial cells in vitro. Hp is a successful commensal organism but lacks the flexibility of adapting its LPS using repeat-mediated phase variation, potentially limiting its range of host niches.